(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The water crisis in India is an exigent issue that has been enhanced by factors such as rapid urbanisation, industrialisation and population growth. The country is suffering from acute water scarcity accompanied by droughts and water shortages in several parts. The lack of clean and safe water has led to multifarious health issues besides waterborne diseases. Pollution from industries and agriculture has diminished water quality, rendering it unsafe for consumption. Israel, a country that has effectively overcome its water crisis, can serve as a valuable model for India and other countries facing this issue. The various pioneering technologies used for tiding water crisis have ensured the country a sustainable water supply for its population. Against this backdrop, the paper is an attempt to examine the notable successes of Israel in implementing innovative water management strategies that played a crucial role in addressing and overcoming its water crisis. The paper concludes that by adopting similar initiatives, India and other countries can improve their water management practices and mitigate the water crisis